A color conversion film including an inorganic separation layer
By using an inorganic partition layer to separate the green perovskite crystal layer and the red core-shell quantum dot layer in liquid crystal display, the problem of components degradation in humidity and oxygen in the prior art is solved, achieving higher stability and optics Maintaining performance.
Patent Information
- Application Number
- CN202310218094.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-15
- Filing Date
- 2023-03-08
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-03-08
AI Technical Summary
The luminescent perovskite crystals and core-shell quantum dot components of existing liquid crystal displays are prone to degradation in the presence of humidity and oxygen, resulting in material incompatibility and stability issues, affecting the life of the display.
A color conversion film including a green perovskite crystal layer and a red core-shell quantum dot layer is used, and separated by an inorganic partition layer and a protective layer. The partition layer is made of inorganic materials such as metal oxides, metal nitrides, silicon oxides, etc. Consisting to provide humidity and oxygen barrier properties.
Improves the anti-humidity and anti-oxidation stability of the display, extends the life of the assembly, and maintains optical properties, avoiding material degradation.
Abstract
Description
Technical Field
[0001] The present invention relates to a color conversion film, which comprises a green perovskite crystal layer and a red core-shell quantum dot layer and a specific spacer layer separating the layers. The present invention further provides a method for manufacturing such a film and a device comprising such a film. Background Art
[0002] The most advanced liquid crystal displays (LCDs) or display assemblies include assemblies based on luminescent crystals (quantum dots). In particular, the backlight assembly of such an LCD may include an RGB backlight consisting of red, blue and green light. Today, luminescent crystals (quantum dots) are often used to produce the backlight colors of such backlight assemblies.
[0003] The manufacture of such components faces various challenges. One of the challenges is embedding the light-emitting crystals into the component. Due to the different chemical properties of the light-emitting crystals, there may be incompatibility between various embedded materials including the light-emitting crystals or even between light-emitting crystals embedded in the same material. This incompatibility may cause the materials in the display component to degrade, and therefore the life of such a display may be affected.
[0004] Additionally, assemblies based on light-emitting crystals often face challenges related to moisture and / or oxygen degradation. Luminescent perovskite crystals are primarily degraded by the presence of moisture / water, and luminescent core-shell quantum dots are primarily degraded by the presence of oxygen. It is difficult to achieve sufficient stability against moisture and oxygen for display assemblies containing green-emitting perovskite crystals and red-emitting core-shell quantum dots. Summary of the invention
[0005] The problem to be solved by the present invention is to overcome the shortcomings of the prior art. In particular, the present invention overcomes the shortcomings of the prior art in terms of stability.
[0006] Unless otherwise stated, the following definitions shall apply in this specification:
[0007] The terms "a", "an", "the" and similar terms used in the context of the present invention should be construed to cover both the singular and the plural, unless otherwise specified herein or clearly contradicted by the context. The term "comprising" should include all of the following: "including", "consisting essentially of" and "consisting of". Percentages are expressed in weight %, unless otherwise specified herein or clearly contradicted by the context. "Independently" means that a substituent / ion can be selected from one of the specified substituents / ions, or a combination of more than one of the above.
[0008] The term "luminescent crystal" (LC) is known in the art and in the context of the present invention refers to crystals of 2-100 nm and made of semiconductor materials. The term includes quantum dots, typically 2-10 nm, and nanocrystals, typically 10-100 nm.
[0009] As the term indicates, LCs exhibit luminescence. In the context of the present invention, the term luminescent crystal includes both single crystal and polycrystalline particles. In the latter case, a particle may contain several crystal domains (grains) connected by crystalline or amorphous phase boundaries. A luminescent crystal is a semiconductor material that exhibits a direct band gap (typically 1.1-3.8 eV, more typically 1.4-3.5 eV, and even more typically 1.7-3.2 eV). When irradiated with electromagnetic radiation equal to or higher than the band gap, valence band electrons are excited to the conduction band, leaving electron holes in the valence band. The formed excitons (electron-electron hole pairs) then undergo radiative recombination in the form of photoluminescence, with a maximum intensity centered at the LC band gap value and exhibiting a photoluminescence quantum yield of at least 1%. When in contact with an external source of electrons and electron holes, LCs can exhibit electroluminescence.
[0010] The term "quantum dot" (QD) is known and refers in particular to semiconductor nanocrystals, which are typically 2-10 nm in diameter. In this range, the physical radius of the QD is smaller than the bulk excitation Bohr radius, resulting in a dominant quantum confinement effect. Therefore, the electronic state of the QD, as well as the band gap, is a function of the QD composition and physical size, i.e., the color absorbed / emitted is related to the size of the QD. The optical quality of a QD sample is directly related to its homogeneity (more monodisperse QDs will have a smaller luminescent FWHM). When the QD reaches a size greater than the Bohr radius, the quantum confinement effect is hindered and the sample may no longer emit light, as non-radiative pathways for exciton recombination may become dominant. Therefore, quantum dots are a specific subgroup of nanocrystals, specifically defined by their size and size distribution. Typical quantum dot compositions include cadmium or indium, for example in the form of cadmium selenide (CdSe) indium phosphide (InP).
[0011] The term "core-shell quantum dots" is known and relates in particular to quantum dots that typically include an indium-containing or cadmium-containing core, typically a CdSe core or an InP core, with an additional shell that typically contains zinc sulfide (ZnS), zinc selenide (ZnSe), cadmium sulfide (CdS) or a combination thereof. Core-shell quantum dots may include multiple shells or a shell gradient.
[0012] The term "perovskite crystal" is known and refers in particular to a crystalline compound comprising a perovskite structure. The perovskite structure itself is known and is described by the general formula M 1 M 2 X 3 Cubic, pseudocubic, tetragonal or orthorhombic crystals, where M 1 M is a cation with a coordination number of 12 (cuboctahedron), M2 is a cation with a coordination number of 6 (octahedron), and X is an anion in a cubic, quasi-cubic, tetragonal or orthorhombic position in the lattice. In these structures, selected cations or anions can be replaced by other ions (randomly or regularly up to 30 atomic %), thereby producing doped perovskites or non-stoichiometric perovskites, but still maintaining their original crystal structure. Preferably, the luminescent perovskite crystals are approximately isometric (such as spherical or cubic). If the aspect ratio of all 3 orthogonal dimensions (longest: shortest direction) is 1-2, the particles are considered to be approximately isometric. Accordingly, the components of the LC preferably include 50-100% (n / n), preferably 66-100% (n / n) more preferably 75-100% (n / n) isometric nanocrystals.
[0013] The production of such light-emitting perovskite crystals is known, for example from WO 2018 / 028869.
[0014] The term "polymer" is known and includes organic and inorganic synthetic materials containing repeating units ("monomers"). The term "polymer" includes homopolymers and copolymers. In addition, crosslinked polymers and non-crosslinked polymers are also included. Depending on the context, the term polymer should include its monomers and oligomers. For example, polymers include acrylic polymers, carbonate polymers, sulfone polymers, epoxy polymers, vinyl polymers, polyurethane polymers, imide polymers, ester polymers, furan polymers, melamine polymers, styrene polymers, norbornene polymers, silazane polymers, silicone polymers and cycloolefin copolymers. According to the practice in the art, polymers may include other materials such as polymerization initiators, stabilizers and fillers.
[0015] The present invention First aspectA color conversion film is disclosed, which can emit green and red light under the excitation of blue light. The film of the present invention comprises multiple layers, wherein one layer is a green light-emitting polymer layer, which comprises green light-emitting perovskite crystals; one layer is a red light-emitting polymer layer, which comprises red light-emitting core-shell quantum dots containing indium or cadmium; wherein the red and green light-emitting polymer layers are separated by one or more separation layers. Suitable separation layers are composed of inorganic materials and cover the entire area of the red and / or green light-emitting polymer layers. In addition, the color conversion film may include one or more protective layers attached to the red light-emitting polymer layer and / or the green light-emitting polymer layer. In addition, the color conversion film may include one or more non-emissive polymer layers.
[0016] This aspect of the invention will be described in further detail below.
[0017] Color conversion film
[0018] Color conversion films are known per se and find widespread application in commercial projects such as displays. According to the invention, the film partially or completely converts blue light into red and green light. Typically, the blue light is partially converted so that light of the blue, green and red spectra is emitted. By adjusting the blue light intensity, concentration, film thickness and the amount of green and red material that emits light, the color of the emitted light can be adjusted according to the needs of the customer.
[0019] The color conversion film may be described as a laminate structure, and its individual layers may be identified, such as "red light-emitting polymer layer," "green light-emitting polymer layer," "spacer layer," and "protective layer," as well as an optional "non-light-emitting polymer layer."
[0020] The film thickness of the color conversion film (including all individual layers) is typically 10-500 microns, preferably 20-250 microns, most preferably 30-200 microns.
[0021] The color conversion films of the present invention can be assembled to obtain a display backlight assembly. Thus, the present invention also provides a display backlight assembly comprising the color conversion film described herein.
[0022] The color conversion films of the present invention can be assembled to obtain a light emitting device, such as a liquid crystal display. Accordingly, the present invention also provides a light emitting device, preferably a liquid crystal display, comprising the color conversion film described herein.
[0023] Separator :
[0024] Separator layers are often applied in laminate structures and color conversion films. As the name suggests, their function is to spatially separate two layers.
[0025] According to the present invention, the separation layer consists essentially of or consists of an inorganic material. Suitable inorganic materials may be selected from the group consisting of metal oxides, metal nitrides, silicon oxides and silicon nitrides. Suitable inorganic materials include but are not limited to SiO x (x=1.7-2.3), AlO x (x = 1.3-1.7) and Si x N y (x=3 and y=3.5-4.5).
[0026] In the context of the present invention, the spacer layer completely or substantially completely covers one surface of the first light-emitting polymer layer. In the field of film production, it is well known that sections at the borders of the laminate structure are not coated with functional layers to allow or facilitate production ("spare areas"). Even if such non-coated areas are present, the skilled person will understand that, except for the spare areas, the laminate structure (i.e. the color conversion film) is completely covered by the spacer layer. The area of the spare areas is typically less than 5% of the total area of the laminate structure.
[0027] In the context of the present invention, the spacer layer is arranged between the first and second light-emitting layers. The spacer layer and the light-emitting layer may be in direct contact or separated by one or more non-light-emitting polymer layers.
[0028] In the context of the present invention, a separator layer is a continuous layer. As the term further indicates, the layer is non-porous and defect-free. Typically, the thickness of such a layer is from 1 nm to 10 microns, preferably from 10 nm to 1 micron. Typically, the thickness of such a layer is more than 10 nm. When composed of the materials described herein, the layer exhibits gas barrier properties, particularly to oxygen and water vapor.
[0029] In an advantageous embodiment, the barrier layer provides a moisture barrier property. In some embodiments, the barrier layer has a water vapor transmission rate (WVTR) of less than 10 g / m 2 *Day, preferably less than 1g / m 2 *Day, most preferably less than 0.1g / m 2 * Days. WVTR can be determined according to ISO 15106-3:2003 at a temperature / relative humidity of 40°C / 90% rh.
[0030] In an advantageous embodiment, the separator layer provides oxygen barrier properties. In some embodiments, the oxygen transmission rate (OTR) is less than 10 cm 3 / m 2 *Days, preferably less than 1cm 3 / m 2 *Days, most preferably less than 0.1cm 3 / m 2* Days. OTR is determined according to ISO 15105 at a temperature of 23°C / 90% rh and atmospheric pressure.
[0031] It was found that optical properties were not negatively affected by including one or more spacer layers as discussed herein. Rather, film stability was improved and favorable optical properties were retained.
[0032] Protective layer:
[0033] A protective layer is often applied in laminate structures and color conversion films. As the name implies, its function is to protect the more sensitive layers in the laminate structure. Therefore, the protective layer is located outside the luminescent layer, for example, as a top layer and / or bottom layer. Apart from its position in the laminate structure, its chemical composition and other properties are the same as the above-mentioned separation layer. Therefore, the protective layer is essentially composed of or consists of inorganic materials. In the context of the present invention, the protective layer is a continuous layer. As the term further indicates, the layer is non-porous and defect-free. Typically, the thickness of the layer is from 1 nm to 10 microns, preferably from 10 nm to 1 micron.
[0034] When composed of the materials described herein, the layer exhibits gas barrier properties, particularly to oxygen and water vapor. In addition, such a protective layer improves the mechanical integrity of the laminated structure and color conversion film of the present invention. It was found that the optical properties are not negatively affected by the inclusion of one or more protective layers. On the contrary, the mechanical stability is improved and the optical properties are retained.
[0035] In one advantageous embodiment, a color conversion film as described herein is provided, comprising one or more first protective layers attached to the red light emitting polymer layer opposite the spacer layer; and one or more second protective layers attached to the green light emitting polymer layer opposite the spacer layer.
[0036] Wherein, each protective layer is independently composed of an inorganic material; is a continuous layer, preferably has a thickness of 1 nm to 10 micrometers; and covers the entire area of the color conversion film.
[0037] Non-emissive polymer layer:
[0038] Such layers are known in the art and may be included in the color conversion film to improve compatibility, or to improve adhesion, or to facilitate manufacturing. PET films or acrylate films are typical examples of non-emissive polymer layers.
[0039] Green light-emitting polymer layer:
[0040] The green light emitting crystal is a perovskite crystal selected from the compounds of formula (I):
[0041] [M 1 A 1]aM 2 b X c (I), wherein:
[0042] A 1 represents one or more organic cations, in particular formamidinium cation (FA),
[0043] M 1 represents one or more alkali metals, in particular Cs,
[0044] M 2 Represents one or more except M 1 Other metals, especially Pb,
[0045] X represents one or more anions selected from the group consisting of halides, pseudohalides and sulfides, in particular Br.
[0046] a represents 1-4,
[0047] b represents 1-2,
[0048] C stands for 3-9, and
[0049] Among them, M 1 , or A 1 , or M 1 and A 1 Both exist.
[0050] In another advantageous embodiment of the present invention, the green light-emitting crystal is a green light-emitting perovskite crystal of formula (I'):
[0051] FAPbBr3(I').
[0052] In particular, formula (I) describes a perovskite light-emitting crystal that, after absorbing blue light, emits light in the green spectrum with a wavelength of 500 nm to 550 nm, particularly in the green spectrum centered at 525-535 nm.
[0053] Suitable polymers may be selected from acrylates and methacrylates.
[0054] Red light-emitting polymer layer:
[0055] Red core-shell quantum dots are known, which emit red light (630 nm + / - 30 nm) when excited by shorter wavelength light. Suitable crystals are selected from II-VI semiconductor compounds and III-V semiconductor compounds.
[0056] In a preferred embodiment, the preferred red emitting core-shell quantum dots have a core comprising indium or cadmium, most preferably indium.
[0057] In another preferred embodiment, the red emitting core-shell quantum dots have a core comprising indium phosphide or cadmium selenide, most preferably indium phosphide.
[0058] Suitable polymers may be selected from acrylates and methacrylates.
[0059] The crystal size of red core-shell quantum dots can vary over a wide range, but is typically 1-10 nm. Such crystals are called quantum dots to distinguish them from microcrystals. For II-VI semiconductor compounds, a suitable range is 1-10 nm, preferably 3-8 nm. For III-V semiconductor compounds, a suitable range is 1-8 nm, preferably 2-4 nm.
[0060] Advantageous implementation methods:
[0061] Preferably, the luminescent crystals (perovskites and core-shell QDs) exhibit a monodisperse size distribution. In the context of the present invention, the term "monodisperse" refers to a population of quantum dots wherein at least about 60% of the population, preferably 75% to 90% of the population, or any integer or non-integer therebetween, falls within a specified particle size range. The diameter deviation of a monodisperse population of particles is less than 20% root mean square (rms), more preferably less than 10% rms, and most preferably less than 5% rms. Particle size and particle size distribution can be determined by microscopy.
[0062] In another advantageous embodiment of the present invention, the green light-emitting polymer layer has 2 The concentration of M in the red light emitting polymer layer is 100-1000ppm, preferably 300-1000ppm, most preferably 500-1000ppm 3 +M 3 'The concentration is greater than 300 ppm, preferably greater than 600 ppm, most preferably greater than 1'200 ppm and / or the red core-shell quantum dots have a platelet structure.
[0063] In another advantageous embodiment of the present invention, the particular size of the red core-shell quantum dots is p 1nm≤s p ≤10nm, especially 3mn≤s p ≤8nm, especially 2nm≤s p ≤6nm, especially 2nm≤s p ≤4nm.
[0064] In another advantageous embodiment, the green light-emitting polymer has a molar ratio z of the sum of (oxygen + nitrogen + sulfur + phosphorus) to carbon, wherein z≤0.9, z≤0.75, in particular z≤0.4, in particular z≤0.3, in particular z≤0.25. The z value is a measure of the polarity of the polymer. A value of z≤0.3 indicates a non-polar polymer. Studies have found that the polarity of the polymer affects the performance of the film, and a lower polarity of the polymer of the green light-emitting film can improve the performance. Preferably, the z value z of the polymer in the green light-emitting layer is 绿 Lower than the z value of the polymer in the red emitting layer 红 Preferably, z 绿 :z 红 <1:2; more preferably, z 绿 :z 红 <1:5.
[0065] In a further advantageous embodiment, the green and / or red emitting polymer comprises an acrylate, very particularly wherein the polymer comprises a cycloaliphatic acrylate or a cycloaromatic acrylate.
[0066] In an advantageous embodiment, the solid polymer comprises an acrylate selected from the group consisting of isobornyl acrylate (CAS 5888-33-5), isobornyl methacrylate (CAS 7534-94-3), dicyclopentyl acrylate (CAS 79637-74-4, FA-513AS (Hitachi Chemical, Japan)), dicyclopentyl methacrylate (CAS 34759-34-7, FA-513M (Hitachi Chemical, Japan)), 3,3,5-trimethylcyclohexyl acrylate (CAS 86178-38-3), 3,3,5-trimethylcyclohexyl methacrylate (CAS 7779-31-9), 4-tert-butylcyclohexyl acrylate (CAS 84100-23-2), 4-tert-butylcyclohexyl methacrylate (CAS 46729-07-1).
[0067] In a further advantageous embodiment, the polymers of the green and / or red emitting polymer layer are crosslinked.
[0068] In a further advantageous embodiment, the polymer of the green and / or red emitting polymer layer comprises a multifunctional acrylate.
[0069] The films of the present invention can be made using commercially available starting materials and lamination steps known to the skilled person. The examples provided below illustrate such a manufacturing process.
[0070] structure:
[0071] The membranes of the present invention may be implemented in a variety of different configurations.
[0072] In a first embodiment, the film of the present invention includes, in addition to the red and green light-emitting polymer layers, a first inorganic protective layer, a second inorganic protective layer and an inorganic spacer layer. It should be understood that one or more additional layers may be present, such as an adhesive layer or other non-light-emitting polymer layer.
[0073] In a second embodiment, the film of the present invention includes, in addition to the red and green light-emitting polymer layers, a first inorganic protective layer, a second inorganic protective layer and two inorganic spacer layers between the light-emitting layers. It should be understood that one or more additional layers may be present, such as an adhesive layer or other non-light-emitting polymer layers.
[0074] In a third embodiment, the film of the present invention comprises a plurality of layers, wherein a non-luminescent polymer layer is provided between one or more inorganic layers and the green and red luminescent polymer layers. In this embodiment, direct contact of the luminescent polymer layer and the inorganic spacer / protective layer is avoided by introducing one or more non-luminescent polymer layers.
[0075] In another embodiment, the film of the present invention comprises the following layer sequence: inorganic protective layer / green light-emitting polymer layer / inorganic spacer layer / red light-emitting polymer layer / inorganic protective layer.
[0076] In another embodiment, the film of the present invention comprises the following layer sequence: inorganic protective layer / one or more non-luminescent polymer layers / green luminescent polymer layer / one or more non-luminescent polymer layers / inorganic spacer layer / red luminescent polymer layer / inorganic protective layer; or
[0077] In another embodiment, the film of the present invention comprises the following layer sequence: inorganic protective layer / one or more non-luminescent polymer layers / green luminescent polymer layer / one or more non-luminescent polymer layers / inorganic spacer layer / non-luminescent polymer layer / red luminescent polymer layer / non-luminescent polymer layer / inorganic protective layer. Example
[0078] Example 1: Preparation of a color conversion film according to the invention having an inorganic barrier layer (inorganic spacer layer) between a green-emitting polymer layer and a red-emitting polymer layer.
[0079] Formation of green ink: A green perovskite luminescent crystal with a formamidinium lead tribromide (FAPbBr3) component was synthesized in toluene in the following manner: Formamidinium lead tribromide (FAPbBr3) was synthesized by grinding PbBr2 and FABr. That is, 16 mmol PbBr2 (5.87 g, 98% ABCR, Karlsruhe (Germany)) and 16 mmol FABr (2.00 g, Greatcell Solar Materials, Queanbeyan, (Australia)) were ground together with yttrium stabilized zirconia beads (5 mm in diameter) for 6 hours to obtain pure cubic FAPbBr3 determined by XRD. The orange FAPbBr3 powder was added to oleylamine (80-90, AcrosOrganics, Hull (Belgium)) (weight ratio FAPbBr3: oleylamine = 100: 15) and toluene (> 99.5%, ultra-pure, Sigma Aldrich). The final concentration of FAPbBr3 was 1 wt%. The mixture was then dispersed by ball milling with yttrium-stabilized zirconia beads with a diameter of 200 μm under ambient conditions (if not otherwise defined, the atmospheric conditions for all experiments were: 35°C, 1 atm, in air) for 1 hour to obtain a green luminescent ink.
[0080] Formation of the green light-emitting polymer layer: 0.1 g of the green ink was mixed with a UV curable monomer / crosslinker mixture (0.7 g FA-513AS, Hitachi Chemical, Japan / 0.3 g Miramer M240, Miwon, Korea) containing 1 wt% of the photoinitiator diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (TCI Europe, Netherlands) and 2 wt% of polymeric scattering particles (organopolysiloxane, ShinEtsu, KMP-590) in a high-speed mixer and toluene was evaporated by vacuum (<0.01 mbar) at room temperature. The resulting mixture was then coated with a 50 μm layer thickness on a 25 μm barrier film (supplier: I-components (Korea); SiOx layer on PET substrate) on the inorganic layer side and then laminated with a second barrier film of the same type, where the inorganic layer side is adjacent to the green light-emitting polymer layer. Afterwards, the laminate was UV cured for 60 seconds (UVAcube 100 equipped with a mercury lamp and a quartz filter, Hoenle, Germany). The initial properties of the resulting film showed a green emission wavelength of 526 nm and a FWHM of 22 nm.
[0081] Formation of the red emitting polymer layer: 0.1 g of red emitting crystals (i.e., isometric core-shell QDs with InP core and ZnS shell, 1 wt% suspended in toluene) were mixed with a UV curable monomer / crosslinker mixture (0.5 g FA-DCPA, Hitachi Chemical, Japan / 0.5 g Miramer M2372, Miwon, Korea) containing 1 wt% of the photoinitiator diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (TCI Europe, Netherlands) and 2 wt% of polymeric scattering particles (organopolysiloxane, Shin-Etsu, KMP-590) in a high-speed mixer and toluene was evaporated by vacuum (<0.01 mbar) at room temperature. The resulting mixture was then coated with a 50 μm layer thickness on the PET side of the barrier film on the green emitting film and then laminated with the same type of barrier film used before, with the inorganic layer side adjacent to the red emitting polymer layer. Afterwards, the laminate was UV cured for 60 seconds (UVAcube 100 equipped with a mercury lamp and a quartz filter, Höller, Germany). The initial properties of the resulting film showed a red emission wavelength of 630 nm and a FWHM of 45 nm.
[0082] Cut pieces of the color conversion films prepared as described above were tested for film stability for 1'000 hours in a climate chamber at 60°C and 90% relative humidity. The so-called edge intrusion of the green and red emitting polymer layers was then measured (edge intrusion refers to the dead edges of degraded perovskite crystals and / or core-shell quantum dots due to diffusion of oxygen and / or humidity from the edge of the film to the center of the film).
[0083] Change of edge intrusion results at 60°C / 90% rH for 1'000 hours:
[0084] -Green edge intrusion: 0.7mm
[0085] -Red edge intrusion: 0.5mm
[0086] These results indicate that a color conversion film can be obtained in which both the green and red light-emitting polymer layers exhibit good resistance to edge intrusion under high temperature / high humidity conditions. The green and red emission wavelengths remain unchanged after the high temperature / high humidity test.
[0087] Comparative Example to Example 1: A color conversion film was prepared which did not have an inorganic barrier layer (inorganic spacer layer) between the green-emitting polymer layer and the red-emitting polymer layer.
[0088] The process is the same as that in the previous embodiment 1, except that the following steps are adjusted:
[0089] - The green light emitting polymer layer is laminated with only one barrier film. The second film used for lamination is a PET film.
[0090] -After the green layer has been UV-cured, the PET film is removed from the sandwich structure.
[0091] - A red light emitting polymer layer is then formed directly on the green light emitting polymer layer and subsequently laminated with a barrier film prior to UV curing of the red layer, as shown in Example 1.
[0092] The emission wavelengths and FWHM of green and red are the same as in Experiment 1.
[0093] Cut pieces of the prepared quantum dot color conversion film were tested for film stability for 1'000 hours in a climate chamber at 60°C and 90% relative humidity. The edge intrusion of the green and red emitting polymer layers was then measured.
[0094] Change of edge intrusion results at 60°C / 90% rH for 1'000 hours:
[0095] -Green edge intrusion: 0.7mm
[0096] -Red edge intrusion: 2.0mm
[0097] These results indicate that a color conversion film without an inorganic spacer layer between the green and red emitting polymer layers results in significant edge intrusion of the red emitting polymer layer.
Claims
1. A color conversion film that emits green light and red light under the stimulation of blue light; the film comprises multiple layers, wherein: One layer is a green light-emitting polymer layer, which includes green light-emitting perovskite crystals; as well as A layer is a red light-emitting polymer layer, which includes red light-emitting core-shell quantum dots containing indium and / or cadmium; and The red light emitting polymer layer and the green light emitting polymer layer are separated by one or more separation layers; and one or more first protective layers positioned adjacent to the red light emitting polymer layer and opposite to the spacer layer; and One or more second protective layers, located adjacent to the green light-emitting polymer layer and opposite to the spacer layer; and Optionally, one or more non-luminescent polymer layers are disposed between the red luminescent layer and the protective layer, and / or one or more non-luminescent polymer layers are disposed between the green luminescent layer and the protective layer; It is characterized in that at least one of the separation layers and each protective layer are independently consisting of an inorganic material independently selected from the group consisting of metal oxides, metal nitrides, silicon oxides and silicon nitrides; and is a continuous layer having a thickness of 1 nm to 10 microns; and Cover the entire area of the color conversion film.
2. The color conversion film according to claim 1, wherein the separation layer has Less than 10g / m 2 * Water vapour transmission rate (WVTR) per day (measured according to ISO 15106-3:2003 at 40°C / 90% rh); and / or Less than 10cm 3 / m 2 Oxygen transmission rate (OTR) *day*bar (determined according to ISO 15105 at temperature 23°C / 90% rh and atmospheric pressure).
3. The color conversion film of claim 1, wherein the spacer layer or the protective layer is independently selected from the following group of materials: SiO x (x=1.7-2.3),AlO x (x=1.3-1.7),Si x N y (x=3 and y=3.5-4.5). 4 . The color conversion film of claim 1 , wherein the polymer of the green light-emitting polymer layer and / or the red light-emitting polymer layer independently comprises acrylate or methacrylate.
5. The color conversion film of claim 1, wherein the perovskite is selected from formamidinium lead bromide (FAPbBr3); and / or the core-shell quantum dots are selected from core-shell quantum dots containing indium.
6. The color conversion film according to claim 1 - having a total film thickness of 10 to 500 microns; and / or -in, One or more non-emissive polymer layers are disposed between the red emitting layer and the spacer layer; and / or - wherein one or more non-emissive polymer layers are disposed between the green emitting layer and the spacer layer.
7. The color conversion film of claim 1, having a total film thickness of 20-250 microns.
8. The color conversion film of claim 1, having a total film thickness of 30-200 microns.
9. The color conversion film of claim 1, comprising multiple layers, including: A first inorganic protective layer, a second inorganic protective layer and an inorganic separator layer; or A first inorganic protective layer, a second inorganic protective layer and two inorganic separation layers.
10. The color conversion film of claim 1, comprising one or more non-emissive polymer layers disposed between the inorganic protection / spacer layer and the emissive layer.
11. The color conversion film of claim 1, comprising multiple layers, the order of the layers being: a. Inorganic protective layer / green light-emitting polymer layer / inorganic separator layer / red light-emitting polymer layer / inorganic protective layer; or b. Inorganic protective layer / one or more non-luminescent polymer layers / green luminescent polymer layer / one or more non-luminescent polymer layers / inorganic separator layer / red luminescent polymer layer / inorganic protective layer; or c. Inorganic protective layer / one or more non-luminescent polymer layers / green luminescent polymer layer / one or more non-luminescent polymer layers / inorganic separator layer / non-luminescent polymer layer / red luminescent polymer layer / non-luminescent polymer layer / inorganic protective layer.
12. A color conversion film as claimed in any one of the preceding claims, wherein: The polarity of the polymer in the green light-emitting polymer layer is smaller than the polarity of the polymer in the red light-emitting polymer layer, The polarity ratio is represented by z 绿 :z 红 <1∶2; and Where z is determined by the molar ratio of the sum of (oxygen, nitrogen, sulfur and phosphorus) to carbon.
13. A display backlight assembly comprising the color conversion film according to any one of claims 1 to 12.
14. A light emitting device comprising the color conversion film according to any one of claims 1 to 12.
15. The light emitting device of claim 14, wherein the light emitting device is a liquid crystal display.
